2008
DOI: 10.1103/physrevb.77.035206
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-enhanced hole transport in thin polymer light-emitting diodes

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim. The transport of holes in polymer light-emitting diodes ͑PLEDs͒ based on poly͑2-methoxy, 5-͑2Ј ethylhexyloxy͒-p-phenylene vinylene͒ ͑MEH-PPV͒ is investigated as a function of layer thickness. For thicknesses smaller than 100 nm, the current in these thin PLEDs is strongly enhanced as compared to the expected space-charge limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 16 publications
3
49
1
Order By: Relevance
“…2 the low-field mobilities h E 0; T of the samples with various thicknesses are shown in an Arrhenius plot. It is observed that the thinnest devices exhibit not only a higher mobility [16] but also weaker temperature activation. This is consistent with the fact that the thinnest devices have the largest concentration of background carriers that have diffused in from the Ohmic contact.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…2 the low-field mobilities h E 0; T of the samples with various thicknesses are shown in an Arrhenius plot. It is observed that the thinnest devices exhibit not only a higher mobility [16] but also weaker temperature activation. This is consistent with the fact that the thinnest devices have the largest concentration of background carriers that have diffused in from the Ohmic contact.…”
mentioning
confidence: 86%
“…In order to align the Fermi level, charge carriers diffuse from the Ohmic contact into the device. Because of the density dependence of the mobility the hole transport in the device is strongly enhanced, for devices of only 40 nm thickness even more than 1 order of magnitude [16]. As a result, there is always a background of extrinsic charge carriers present in SCL diodes that modify the transport.…”
mentioning
confidence: 94%
“…Various temperature, density, and fielddependent mobility models have been reported. 13,[25][26][27][28][29][30] Here, we assume that charge transport is described by variable range hopping in an exponential DOS. 13 The hole mobility then reads…”
Section: Numerical Device Modelmentioning
confidence: 99%
“…For a complete description, diffusion effects from the contacts, 34 the charge carrier density dependence and field dependence of the mobility need to be taken into account. The occurrence of a SCL current enables us now to also further investigate the densityand field dependence of the hole mobility of PFO.…”
mentioning
confidence: 99%